Optimum reassignment of degrading components for non-repairable systems. (3rd March 2020) - Zhu, Xiaoyan; Fu, Yuqiang; Yuan, Tao
Abstract: The components in a system can degrade differently, due to the operational loads or environmental conditions, or both, in their positions being different. Therefore, reassignment of the functionally exchangeable components to the positions at appropriate time can increase system reliability and extend system lifetime. In this article, a new component reassignment problem is proposed, and a mixed binary nonlinear programming model is built to determine the optimal reassignment time and optimal reassignment of degrading components with the objective of maximizing system lifetime. The model integrates continuous optimization and combinatorial optimization, and provides a framework for optimizing the component reassignment decisions for various degradation models and system structures. Furthermore, the optimization model and analytical results are derived for k- out-of- n systems of linearly degrading components or exponentially degrading components. The analytical results reduce the complexity of solving the optimization model and are used to design an efficient solution method. Finally, numerical examples in a power supply system demonstrate applications of the optimization model and further provide managerial insights for the component reassignment problem of degrading components.